Investigating Mangrove-Based Tourism in Sambelia District: Potentials and Challenges - Yogi Birrul Walid Sugandi; Budi Setiawan (LPPM Institut Pendidikan Nusantara Global, 2025)
In Indonesia, many mangrove-rich regions remain underutilized for tourism, particularly in less-developed coastal districts. Sambelia District in East Lombok represents one such area, where extensive mangrove ecosystems offer significant opportunities but also face complex development challenges. This study aims to examine the economic, social, and environmental potential of mangrove-based tourism in Sambelia District, as well as to identify key challenges that hinder its sustainable development. A mixed-methods approach was employed to provide a comprehensive understanding of these issues. Quantitative data were collected through questionnaires distributed to 36 respondents; local community members and tourism stakeholders, while qualitative data were obtained through focus group discussions and semi-structured interviews with six key informants involved in mangrove management and tourism activities. The data were analyzed descriptively and thematically to capture both measurable trends and in-depth perspectives. The findings indicate that mangrove-based tourism in Sambelia has strong potential to increase local income, create employment opportunities, stimulate small businesses, and support environmental conservation. Social benefits include strengthened community cooperation, increased local pride, and opportunities for knowledge exchange, although participation among youth and women remains limited. Despite these potentials, several challenges persist, including low community awareness and capacity, weak stakeholder collaboration, short-term government programs, environmental degradation, and inadequate infrastructure. This study contributes to the limited literature on mangrove tourism development in emerging destinations by highlighting the conditions required to balance conservation and community-based tourism.